Surgical rehabilitation of patients with Crohn’s disease - Poyda, O. I.; Melnyk, V. M. (General Surgery, 2024)
Objective — to enhance the outcomes of surgical rehabilitation for patients with Crohn’s disease through the improvement and implementation of organisational measures as well as general and specialised surgical strategies. Materials and methods. The study focused on the development of organisational measures as well as general and specialised surgical rehabilitation procedures for Crohn’s disease. The research was conducted to determine the scope of radical surgical interventions for complications resulting from segmental lesions with extensive damage to the intestinal tract. The study also aimed to develop methods of restorative, reconstructive and restorative operations that would reduce the frequency of postoperative complications, disease recurrence, digestive disorders in the intestinal tract, malabsorption, and anal incontinence. Additionally, the study aimed to improve the functional outcomes and quality of life for operated patients. Results. A total of 53 patients with Crohn’s disease — 28 (52.8%) men and 25 (47.2%) women — were operated on using specially designed surgical rehabilitation techniques. The patients undergoing surgery ranged in age from 19 to 45. 32 (60.4%) patients had segmental resections, while 21 (39.6%) had extensive resections. 8 (15.1%) patients underwent restorative operations, while 40 (75.4%) had reconstructive operations. A lifelong ileostomy was formed in 5 (9.4%) patients. Postoperative complications were observed in 12 (22.6%) patients, and disease relapses in 5 (9.4%) patients. One (1.8%) patient died after surgery. Positive functional outcomes, including improved digestion in the intestinal tract, normal absorption, and preservation of anal retention, were noted following restorative and reconstructive‑restorative operations. Conclusions. Organisational measures as well as general and specialised surgical rehabilitation strategies for Crohn’s disease allowed for more effective diagnosis and treatment of postoperative complications, better prevention of disease recurrence, improved digestion in the intestinal tract, normalised absorption processes, and preservation of anal retention. Following the implementation of specially designed surgical rehabilitation techniques, 20.7% and 1.8% of patients experienced early and late postoperative complications, respectively. Additionally, there were occurrences of postoperative mortality in 1.8% of patients and relapses in 9.4%. Severe forms of reflux ileitis, postcolectomy syndrome, and secondary anal incontinence syndrome were not observed.